Serodiagnosis of Recently Acquired Toxoplasma gondii Infection with a Recombinant Antigen - Li, Shuli (American Society for Microbiology, 2000)
A portion of a cDNA encoding a 35-kDa antigen from Toxoplasma gondii was cloned into the CKS expression vector and expressed in Escherichia coli. By using the enzyme-linked immunosorbent assay (ELISA), the recombinant protein (rP35 antigen) was examined for reactivity with immunoglobulin G (IgG) antibodies in the sera of pregnant women. Of these women, 41 had a toxoplasma serologic profile suggestive of recently acquired T. gondii infection (Sabin-Feldman dye test [DT] titers from 1:256 to 1:32,000, positive IgM ELISA titers from 2.3 to 9.7, positive IgA ELISA from 1 to >28, and acute patterns in the differential agglutination [AC/HS] test) (group I), and 50 women had a toxoplasma serologic profile suggestive of infection acquired in the distant past (low DT titers from 1:16 to 1:512, negative IgM ELISA titers from 0 to 0.8, and chronic patterns in the AC/HS test) (group II). The classification of acute or chronic profile was based on the individual's clinical history as well as the combination of the results of the toxoplasma serological profile. An additional group (group III) was composed of sera from 50 women who were seronegative for T. gondii antibodies in the DT. The results revealed that whereas 85.3% of women in group I had IgG antibodies that reacted with the rP35 antigen, only 8% of women in group II had IgG antibodies that reacted with the same antigen. In immunoblots, the rP35 antigen was recognized by IgG antibodies in a pool of sera from individuals with a toxoplasma serologic profile compatible with acute infection but not in a pool of sera from individuals with a serologic profile characteristic of a chronic infection. These results reveal that IgG antibodies against the P35 antigen are produced during the acute stage of the infection but are uncommon in the latent or chronic phase of the infection. Thus, the rP35 antigen may be a useful serologic marker to differentiate between recently acquired infection and that acquired in the more distant past.